Formulation of the Polysaccharide FucoPol into Novel Emulsified Creams with Improved Physicochemical Properties - Sílvia Baptista; Filomena Freitas (Molecules, 2022)
Driven by the customers’ growing awareness of environmental issues, the production of topical formulations based on sustainable ingredients is receiving widespread attention from researchers and the industry. Although numerous sustainable ingredients (natural, organic, or green chemistry-derived compounds) have been investigated, there is a lack of comparative studies between conventional ingredients and sustainable alternatives. In this study, olive oil (30 wt.%) and α-tocopherol (2.5 wt.%) containing oil-in-water (O/W) emulsions stabilized with the bacterial fucose-rich polysaccharide FucoPol were formulated envisaging their validation as cosmetic creams. After formula composition design by Response Surface Methodology (RSM), the optimized FucoPol-based emulsion was prepared with 1.5 wt.% FucoPol, 1.5 wt.% cetyl alcohol, and 3.0 wt.% glycerin. The resulting emulsions had an apparent viscosity of 8.72 Pa.s (measured at a shear rate 2.3 s−1) and droplet size and zeta potential values of 6.12 µm and −97.9 mV, respectively, which are within the values reported for cosmetic emulsified formulations. The optimized formulation displayed the desired criterium of a thin emulsion system, possessing the physicochemical properties and the stability comparable to those of commercially available products used in cosmeceutical applications.